Are the Average Effects of Foster Care Placement Really Close to Zero?. (July 2022) - Wakefield, Sara; Wildeman, Christopher
In their provocative article, Barth and colleagues interrogate existing research on a series of claims about the child welfare system. In this reply, we focus on just one of their conclusions: that foster care placement does little, on average, to cause the poor outcomes of children who are ever placed in care. Our argument proceeds in three stages. In the first, we dispute the claim that the average effects of foster care placement on children are "settled" in any scientific sense. In the second, we note that the lack of agreement about what constitutes the appropriate counterfactual makes the idea of average effects of foster care placement in this area problematic. In the third, we problematize the idea that near-zero average effects equate to unimportant effects by showing how different types of effect heterogeneity may lead us to think differently about how the system is working.